2018
DOI: 10.1177/0194599818756592
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Transcanal Transpromontorial Approach: A Novel Surgical Technique for Cerebellopontine Angle Vestibular Schwannoma Removal

Abstract: Objective Vestibular schwannoma (VS) is a benign tumor of the lateral skull base. Different microscopic surgical techniques are described in literature: the retrosigmoid and translabyrinthine approaches are used to treat big tumors located in the cerebellopontine angle, and the middle cranial fossa approach is utilized for small tumors with good hearing preservation. The expanded transcanal transpromontorial (ExpTT) approach is a combined microscopic-endoscopic technique previously indicated for Koos stage I a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Presutti et al (16) concluded that expanded ETTA (using both endoscope and microscope, which allows bimanual dissection of the tumor and therefore, enhanced control of the surrounding neurovascular structures) was successful in the management of 10 patients with vestibular schwannoma Koos stage I or II with no facial dysfunction in the last follow-up. Marchioni et al (9) described the expanded ETTA for the successful resection of vestibular schwannoma in patients with Koos grade II and III with no complication and good facial nerve result and concluded that this technique was a new approach that combined the advantages of a microscopic technique with the ones offered by the endoscope. Moon et al (12) evaluated a modified ETTA with no EAC closure for the treatment of vestibular schwannomas and reported better cosmetic outcome compared to the original technique with total resection of the tumor in all cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Presutti et al (16) concluded that expanded ETTA (using both endoscope and microscope, which allows bimanual dissection of the tumor and therefore, enhanced control of the surrounding neurovascular structures) was successful in the management of 10 patients with vestibular schwannoma Koos stage I or II with no facial dysfunction in the last follow-up. Marchioni et al (9) described the expanded ETTA for the successful resection of vestibular schwannoma in patients with Koos grade II and III with no complication and good facial nerve result and concluded that this technique was a new approach that combined the advantages of a microscopic technique with the ones offered by the endoscope. Moon et al (12) evaluated a modified ETTA with no EAC closure for the treatment of vestibular schwannomas and reported better cosmetic outcome compared to the original technique with total resection of the tumor in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…The lower risk of CSF leakage is because the ETTA is minimally invasive and with limited bone removal (9). The ETTA not only could minimize post-surgery complications but also could be a cost-benefit technique because it could shorten postoperative intensive care unit recovery and hospital stay (9,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When further dissection was needed for the ETTA approach, a blind sac of the EAC was performed. 18,36…”
Section: Treatmentmentioning
confidence: 99%
“…The few reports on the transmeatal approach to acoustic schwannoma are reported in Table I 4,[6][7][8][9][10][11][12][13] . The endoscopic surgery of the middle ear recently evolved into the transcanal endoscopic approach to labyrinth and IAC for schwannoma with good outcomes [14][15][16] . It is universally acknowledged that the endoscope allows excellent visualisation of structures and hidden sites "around the corner".…”
Section: Introductionmentioning
confidence: 99%